A Comparative Study on Distribution, Morphology, and Some Chemical Constituents of Seminal Vesicles in Catfishes - Joy, K. P.; Singh, M. S. (Informatics Publishing Ltd. and Society for Reproductive Biology and Comparative Endocrinology, 2022)
Seminal vesicles (SV) are present in all catfishes collected in this study : Clarias batrachus (Linnaeus), Wallago attu (Bloch and Schneider), Ompok siluroides (Lecepede), Rita rita ((Hamilton), Mystus tengara (Hamilton), Mystus vittatus (Bloch), Pangassius pangassius (Hamilton), Heteropneustes fossilis (Bloch) and absent in species other than catfishes. The number of SV lobes ranged from a single pair in H. fossilis to several pairs in P. pangassius with significant morphological variations. Total proteins, fructose, hexosamines and sialic acid were estimated in the testes and SV. Compared to testes, total proteins were higher in the SV of W. attu, O. siluroides and H. fossilis, fructose levels were higher in the SV of O. siluroides and C. batrachus, hexosamine contents were higher in the SV of W. attu, M. tengara and H. fossilis, and sialic acid levels in the SV of W. attu, O. siluroides, R. rita, M. vittatus and P. pangassius. Sialic acid was not detected in the testes of R. rita and H. fossilis. The SV may be an adaptive modification of the reproductive system for temporary storage of spermatozoa in a protein-sugar-rich nutrient medium.